A Cross-Country Analysis of Gen Z Consumers’ Perceptions towards Sustainable Luxury in Italy and Finland - Gagliardi, Giorgia (My University, 2026)
The worldwide luxury fashion sector is facing a fundamental change in its way of thinking largely due to increased pressures to find a balance between traditional values of exclusivity and craftsmanship and the new demands of environmental and social responsibilities. Although the tension between luxury and sustainability has been the focus of numerous studies, major gaps still exist in the understanding of how national context influences Generation Z’s perception of different Corporate Social Responsibility (CSR) narratives. Most current research consists of single-country studies and treat sustainability as one concept, missing out on how structural differences between societies could affect people’s understanding and judgement of sustainability. The present study seeks to fill the gap by using a quantitative cross-national comparative approach to explore the differences in the perceptions of sustainable luxury between Gen Z consumers in Italy and Finland. Also, the study aims to find out to what extent Humanistic versus Environmental CSR models are prioritised by these young consumers. Italy and Finland are used as examples of structurally different national contexts: Italy is marked as a country where the institutional environment is mainly driven by heritage, craftsmanship, and social embedding. In contrast, Finland is portrayed as a country where the institutional environment is chiefly innovation-driven, environmentally oriented, and system-based. These two styles are then further described through measurable country-level indicators. Primary data was gathered through an online survey based on different scenarios and included 106 Generation Z participants (64 Italians and 42 Finnish). All respondents were presented with two CSR brand scenarios. Non-parametric statistical tests were used for analysing the data, including the Mann-Whitney test for between-group comparisons and the Wilcoxon signed-rank test for within group comparisons, supported by a chi-square test of independence. The findings strongly support both hypotheses. While Gen Z consumers in Italy perceived the Humanistic CSR scenario as much more authentic than their Finnish counterparts, Finnish consumers showed a very strong and large-effect preference for the Environmental CSR narrative in all constructs, including purchase intention. A chi-square test showed that there is a very significant difference between the two countries in overall narratives’ preference. Crucially, the Italian sample showed an intra-group attitude-behaviour gap: although they saw Humanistic CSR as slightly more authentic, Italian respondents did not really alter their purchase intention based on this evaluative preference. These results building on the sustainable luxury idea by revealing that the paradox is resolved in culturally distinct ways: by the human-centred heritage values in Italy and by the circular environmental innovation in Finland. The research questions the idea of one single homogeneous European Generation Z consumer segment and provides luxury brand managers with practical knowledge for context-sensitive “glocal” CSR communication strategies.
Keywords: consumer behaviour; societal responsibility; corporate responsibility; luxury goods; sustainable development; brands; luxury; environmental responsibility; consumption; consumers; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business